The Relationship between the Bank Choice Determinants and the Acceptance of Musharakah Mutanaqisah Home Financing among Malaysian Muslims - Dalfiza Mohd, Yusof; Ahmad Azrin, Adnan; Zakaria, Bahari (2014)
This article aims to analyse the relationship between the bank choice determinants and the acceptance of the MusharakahMutanaqisah home financing among Muslim customers in Terengganu, one of the constitutive state of federal Malaysia. This research focuses on the Shariah-adherent behaviour. It refers to what extent do Muslim customers in Terengganudemonstrate an ideal behaviourconsidering the fact that they are living in a state that practices an Islamic governance system? The data are obtained through questionnaires from 300 respondents. The Pearson correlation test shows a positive direction between the acceptance of MusharakahMutanaqisahhome financing and the bank choice determinants. However, the strength of the relationship between these variables was at a moderate level, which shows the acceptance degree of MusharakahMutanaqisah home financing among Muslims in Terengganu.